Reaching all in rural sanitation: experiences from inclusive programming in five countries. Issue 5 (3rd July 2020) - Carrard, Naomi; Kohlitz, Jeremy; Soeters, Simone; Halcrow, Gabrielle; Murta, Janina; Willetts, Juliet
ABSTRACT: There is a need to reflect on approaches to reaching all in rural sanitation, given evidence that disadvantaged groups often miss out on benefits from programmes. This article presents approaches from area-wide rural sanitation programming undertaken by SNV across five countries. Analysis identified ten strategies used in combination to support inclusion. The article describes the strategies and their application, then presents four implications for the rural sanitation sector: the value of a "toolbox" approach; co-creation of strategies with stakeholders; recognition of local government as a driver of inclusive services; and the need to strengthen evidence on how strategies contribute to success.